Analysis of the Implementation of the National Early Warning Score (NEWS) on Nurses in Handling Follow-up of Emergency Patients through Fast Response Assessment - Sholichin Sholichin; Anik Puji Rahayu; Ediyar Miharja; Mayusef Sukmana (Fakultas Kedokteran, 2021)
Patients who come to the emergency department (ER) show good condition at the beginning of admission, but the status of the patient's condition can change to worsen. Subtle changes in parameters affect acute physiological conditions in patients, such as pulse rate, blood pressure, respiratory rate, and level of consciousness. Poor clinical monitoring and inadequate interpretation of changes in physiological parameters, and failure to prescribe appropriate measures can result in serious adverse events such as cardiac arrest, intensive care unit admission, and even death (Alam, Hobbelink, Van Tienhoven). , Jansma & Nayakkara, 2014). This study aimed to see the effectiveness of the application of NEWS on the assessment of nurses' fast response. This study is a quasi-experimental study with a pre-post approach without group control, namely research that provides intervention to a group of subjects by measuring before after the intervention or without a comparison group. The population in this study were all emergency room nurses at Parikesit Hospital Tenggarong. In this study, the sampling technique used was simple random sampling. Sampling with population members is homogeneous and has the same opportunity to take as a sample. The inclusion criteria in this study were nurses who served in the ER at Abdul Moeis Hospital Samarinda. This study concludes that applying NEWS will be more effective in handling follow-up emergency patients through Fast Response assessment with a p-value < 0.05. The conclusion of this study is the quick response assessment at the Parikesit Tenggarong Hospital before the application of NEWS to patients treated in the Karang Asam and Enggang room. The result shows that 16 nurses (45.7%) were suitable to carry out treatment based on the patient's emergency. After the implementation of NEWS the nurse's response to patient care increased to 74.3%.